2017
DOI: 10.1016/j.bpj.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae in Rabbit Ventricular Myocytes: Distribution and Dynamic Diminution after Cell Isolation

Abstract: Caveolae are signal transduction centers, yet their subcellular distribution and preservation in cardiac myocytes after cell isolation are not well documented. Here, we quantify caveolae located within 100 nm of the outer cell surface membrane in rabbit single-ventricular cardiomyocytes over 8 h post-isolation and relate this to the presence of caveolae in intact tissue. Hearts from New Zealand white rabbits were either chemically fixed by coronary perfusion or enzymatically digested to isolate ventricular myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…We also identified the caveolae in these cells. Note that this lipid raft tends to disappear when other culture techniques are used [33]. Interestingly, the electron microscopy pictures show a rich environment of SR and mitochondria similar to that of ventricular cells [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified the caveolae in these cells. Note that this lipid raft tends to disappear when other culture techniques are used [33]. Interestingly, the electron microscopy pictures show a rich environment of SR and mitochondria similar to that of ventricular cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Note that this lipid raft tends to disappear when other culture techniques are used [33]. Interestingly, the electron microscopy pictures show a rich environment of SR and mitochondria similar to that of ventricular cells [33]. Using the same protocol as [9], we found that when a contraction eliminating substance was not added to the medium, the spontaneous beating rate and Ca 2+ dynamics of pacemaker cells were far from the physiological range and PKA activity was documented to be lower.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mitochondria are capable of accumulating Ca 2+ and may buffer cytosolic Ca 2+ fluctuations (Dedkova & Blatter, 2008), potentially in a mechanically modulated manner (Morad et al, 2005;Belmonte & Morad, 2008;Iribe et al, 2009;Miragoli et al, 2016). A potentially related phenomenon, mitochondrial swelling, may also influence cardiac force development, contractility, and even gene expression, through changes in internal pressure and by affecting the morphology of neighboring organelles (Kaasik et al, 2010;Burton et al, 2017). Microtubules run along the intersarcomeric space and interweave with several mitochondria in a row.…”
Section: Discussionmentioning
confidence: 99%
“…organelles are influenced by deformations resulting from passive cardiomyocyte stretch and active shortening, a process aided by cytoskeletal filaments that bear and transmit mechanical loads throughout the cell (Bartolak-Suki et al, 2017;Ingber, 2008;Robison et al, 2016). As shown for the surface sarcolemma (Kohl et al, 2003;Pfeiffer et al, 2014), some intracellular membranous structures, such as T-tubules, contain "spare membrane" in the shape of caveolae (Burton et al, 2017).…”
mentioning
confidence: 99%
“…Although laborious, electron tomography has been employed in cardiac science for several years [8,29,36]. Cryo-ET has also been used as a diagnostic tool in the clinical setting, helping resolve the fine ultrastructure of airway epithelial cilia in primary ciliary dyskinesia patients [53], and of platelets in the context of malignant cancers [98].…”
Section: Electron Microscopy and Tomographymentioning
confidence: 99%